(untitled) (REM. Chilean Journal of Musical Education, 2025)
This study addresses possibilities for the historiographical production of music teaching practices in Brazil, focusing on inland locations, using as a case study the documentary sources found in the city of Formiga, located in the centrewest of the Brazilian state of Minas Gerais. Mentioning the theoretical-methodological and analytical approaches, the relevance of historical documents, in various types, for musical research is discussed, as well as looking at the spaces and practices in which we can consider the existence of musical education processes. The study focuses on practices identified between the 1930s and 1980s and highlights the importance of documentary research for understanding local contexts, offering possible directions for similar research in other locations that face similar challenges.